Scaling up noncommunicable disease care in a resource-limited context: lessons learned and implications for policy - Yoseph Mamo; Mirchaye Mekoro; David I. W. Phillips; Andrew Mortimore (BMC, 2024)
Abstract Background Although primary care models for the care of common non-communicable diseases (NCD) have been developed in sub-Saharan Africa, few have described an integrated, decentralized approach at the community level. We report the results of a four-year, Ethiopian project to expand this model of NCD care to 15 primary hospitals and 45 health centres encompassing a wide geographical spread and serving a population of approximately 7.5 million people. Methods Following baseline assessment of the 60 sites, 30 master trainers were used to cascade train a total of 621 health workers in the diagnosis, management and health education of the major common NCDs identified in a scoping review (hypertension, diabetes, chronic respiratory disease and epilepsy). Pre- and post-training assessments and regular mentoring visits were carried out to assess progress and remedy supply or equipment and medicines shortages and establish reporting systems. The project was accompanied by a series of community engagement activities to raise awareness and improve health seeking behaviour. Results A total of 643,296 people were screened for hypertension and diabetes leading to a new diagnosis in 24,313 who were started on treatment. Significant numbers of new cases of respiratory disease (3,986) and epilepsy (1,925) were also started on treatment. Mortality rates were low except among patients with hypertension in the rural health centres where 311 (10.2%) died during the project. Loss to follow up (LTFU), defined as failure to attend clinic for > 6 months despite reminders, was low in the hospitals but represented a significant problem in the urban and rural health centres with up to 20 to 30% of patients with hypertension or diabetes absenting from treatment by the end of the project. Estimates of the population disease burden enrolled within the project, however, were disappointing; asthma (0.49%), hypertension (1.7%), epilepsy (3.3%) and diabetes (3.4%). Conclusion This project demonstrates the feasibility of scaling up integrated NCD services in a variety of locations, with fairly modest costs and a methodology that is replicable and sustainable. However, the relatively small gain in the detection and treatment of common NCDs highlights the huge challenge in making NCD services available to all.